2018
DOI: 10.1021/acs.biochem.8b01181
|View full text |Cite
|
Sign up to set email alerts
|

High-Contrast Facile Imaging with Target-Directing Fluorescent Molecular Rotors, the N3-Modified Thioflavin T Derivatives

Abstract: Immunostaining methods have generally been used not only for biological studies but also for clinical diagnoses for decades. However, recently, for these methods, improved rapidity and simplicity have been required for relevant techniques in laboratory research and medical applications. To this end, we present here a novel approach for designing fluorescent molecular rotor probes, i.e., N 3-modified thioflavin T (ThT) derivatives, which enabled specific detection of interesting protein targets with sensitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To verify this hypothesis, we first carried out a ThT displacement assay in vitro to investigate the fluorescence change. ThT is a versatile fluorescent probe, which has been widely used in G4 DNA and RNA visualization due to their distinguished fluorescence enhancement with G4s. As shown in Figure S21, CQ treated with KSS in K + gave a strong emission at 510 nm. Upon gradual addition of ThT, the fluorescence peak was shifted to 495 nm (emission of ThT-G4 complex), indicating that ThT can displace CQ from G4s.…”
Section: Resultsmentioning
confidence: 99%
“…To verify this hypothesis, we first carried out a ThT displacement assay in vitro to investigate the fluorescence change. ThT is a versatile fluorescent probe, which has been widely used in G4 DNA and RNA visualization due to their distinguished fluorescence enhancement with G4s. As shown in Figure S21, CQ treated with KSS in K + gave a strong emission at 510 nm. Upon gradual addition of ThT, the fluorescence peak was shifted to 495 nm (emission of ThT-G4 complex), indicating that ThT can displace CQ from G4s.…”
Section: Resultsmentioning
confidence: 99%
“…We then demonstrated that ThT-HE binds to parallel G4 in particular and exhibits strong fluorescence while maintaining the low background emission properties of ThT [17]. In addition, we reported the application of ThT-HE to G4 detection systems [18][19][20]. Since then, ThT with an ethyl group introduced at the N 3 -position (ThT-E) has been reported by Guan et al [21], but the derivatization of ThT at the N 3 -position has not seen significant progress otherwise.…”
Section: Fluorescence Spectral Analysis Of Tht Tht-he and Tht-aementioning
confidence: 85%
“…The synthesis of ThT-HE is described in [17] and those of ThT-AE and ThT-OE11 are described in [18]. The syntheses of ThT-OE2 and ThT-SP are described in the supplementary materials.…”
Section: Chemical Syntheses Of Tht Derivativesmentioning
confidence: 99%